2018
DOI: 10.1021/acs.chemmater.8b01602
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Surface Composition and Oxygen Reduction Reaction Activities of Pt–Ni Octahedral Nanoparticles by Microwave-Enhanced Surface Diffusion during Solvothermal Synthesis

Abstract: Compositional segregations in shaped alloy nanoparticles can significantly affect their catalytic activity and are largely dependent on their elemental anisotropic growth and diffusion during nanoparticle synthesis. An efficient approach to control the surface segregations while keeping the nanoparticle shape are highly desired for fine-tuning their catalytic properties. Using octahedral Pt−Ni nanoparticles as a typical example, we report a new strategy to modulate the surface composition of shaped bimetallic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…However, it is also found that BA can significantly decrease the NP size and more importantly slows down the reduction kinetics of Ni precursor via forming a new Ni–(BA) complex precursor, leading to a phase separation in the final Pt–Ni NPs. Refining previously well-recognized shape-directing role, 3,6 our results contribute to a deeper understanding on the metal–ligand coordination chemistry and its effect on the elemental growth mechanism and phase separation of bimetallic alloy NPs.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, it is also found that BA can significantly decrease the NP size and more importantly slows down the reduction kinetics of Ni precursor via forming a new Ni–(BA) complex precursor, leading to a phase separation in the final Pt–Ni NPs. Refining previously well-recognized shape-directing role, 3,6 our results contribute to a deeper understanding on the metal–ligand coordination chemistry and its effect on the elemental growth mechanism and phase separation of bimetallic alloy NPs.…”
Section: Introductionsupporting
confidence: 81%
“…1 For instance, there have been intense interests in the synthesis of octahedral PtNi alloy NPs enclosed by {111} facets, which represents one of the state-of-the-art highly active electrocatalyst for the cathodic oxygen reduction reaction (ORR) in fuel cells. 26 Several methods have been successfully developed during past years, including organic phase reduction using oleylamine and oleic acid as the surfactants 4,79 and solvothermal synthesis in a N , N -dimethylformamide (DMF) solvent with or without benzoic acid (BA) as the surfactant. 3,5,10,11 Studying the effect of surfactants on the elemental growth kinetics is critical to guide the morphology and surface compositional control of the shaped alloy NPs.…”
Section: Introductionmentioning
confidence: 99%
“…The strategies to minimize the Pt amount call for a shift from monometallic nanoparticles (NPs) to the use of nano-engineered architectures with tailored morphologies and compositions [ 1 , 2 ]. For instance, bi- or tri-metallic particles, alloys [ 3 , 4 , 5 , 6 ] and successively de-alloyed [ 7 ] structures where Pt is associated with other transition metals (e.g., Ni, Co, Cu) have been prepared and demonstrated high ORR activity and durability. Another very promising class of tailored electrocatalysts is represented by core@shell nanostructures with a thin Pt skin covering a transition metal core in 0D (particle-like) [ 8 , 9 , 10 ] and 1D (fiber-like) morphologies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, several benchmarking strategies have been designed for efficient utilization of Pt, for example, forming Pt‐based alloys, stabilizing the Pt single atom catalyst in conducting supports, and crystal facet engineering to selectively expose ORR active sites . Among them, alloying Pt with low‐cost transition metals (such as Ni, Co, Fe) has been investigated as an effective approach to reduce the Pt loading in advanced ORR catalysts . Fundamental and theoretical research has demonstrated that the enhanced ORR activity of Pt‐based alloys originates from the improved electronic structure, which decreases the adsorption energy of spectator species such as underpotentially deposited hydrogen (H upd ) and hydroxyl (OH ads ), and consequently exposes active sites for oxygen reduction .…”
Section: Introductionmentioning
confidence: 99%